Ethical leadership, ethical climate and integrity violation: A comparative study in Saudi Arabia and Malaysia - Manal Mohammed Hamoudah; Zaleha Othman; Rashidah Abdul Rahman; Nor Azila Mohd Noor; May Alamoudi (Administrative Sciences, 2021)
The primary aim of this study is to investigate the relationship among the ethical leadership, ethical climate and integrity violation of the local government of two countries, Saudi Arabia and Malaysia. Past studies indicate that ethical leadership and ethical climate influenced the integrity of local government. However, studies were mostly conducted in Western countries. Given the lack of comparative studies in Muslim-oriented countries, we intend to fill the gap by building upon previous studies on the relationship between ethical leadership and ethical climate and integrity violation of the local government. The study used survey to collect data from local authorities in the two nations. PLS-SEM was used to analyze the survey data. The findings demonstrated that the relationship between ethical leadership and integrity violation is not significant for Malaysians. Thus, the study assumption is not supported. By contrast, Saudi showed a different result in the relationship between ethical leadership and integrity violation; the relationship between ethical leadership and integrity violation in Saudi is negatively significant. Hence, the assumption is supported for Saudi participants. In regard to the ethical climate, results reveal that for Malaysia and Saudi, ethical climate negatively and significantly influence integrity violation. Thus, the assumption for both countries is supported. The findings of this study are useful for the practical development of local authorities as the findings provide information for the local government to safeguard against integrity violation. The findings also contribute social implications by educating organizations toward the role of ethical climate in preventing integrity violation. In addition, the study contributes to the growing interest in comparative studies.
Keywords: 350; ethical climate; ethical leadership; integrity violation; local government; Malaysia; Saudi Arabia